Influence of Perceived Risk and Value Consciousness on Attitude Towards Music Piracy - Sridhar, G.; Narasimha Murthy, G. (Indian Journal of Marketing, 2017)
Piracy has become a global scourge and its effects are seriously felt on products sold over digital platforms, especially music. It is not surprising if we hear that music is not often purchased with growing presence of torrents on the Internet. Broadly, piracy has been studied both from demand and supply sides, but the demand side has been inadequately researched yet. This paper attempted to explore the consumer (i.e. demand) side with a broad objective to explore the influence of perceived risk and value consciousness on music piracy. A survey on 225 respondents, all being students of management graduation, was conducted using a structured questionnaire. Results of the study indicated that both the variables explained a significant variance in the attitude towards music piracy. Managerial and academic implications were also discussed.